Comorbidities in primary cicatricial alopecia: a systematic review and meta-analysis - Yongpisarn, Tanat; Tejapira, Kasama; Suchonwanit, Poonkiat (Frontiers in Immunology, 2025)
BackgroundPrimary cicatricial alopecia (PCA) is known to be associated with various comorbidities; however, findings regarding the likelihood of specific comorbidities in PCA patients have been inconsistent.ObjectiveThis study aimed to assess the prevalence and odds of specific comorbidities in patients with PCA compared to controls, and to explore the distribution of comorbidities across various types of PCA.MethodsElectronic searches were conducted using PubMed, Embase, and Scopus from the dates of their inception until July 2024. A total of 116 studies with 33,494 PCA patients that reported data allowing for the calculation of odds ratios (OR) or prevalences of certain comorbidities in PCA patients were included.ResultsSystemic lupus erythematosus is more prevalent among patients with lichen planopilaris (LPP) [OR 3.10 (95% confidence interval: 2.24–4.29), prevalence 2%], frontal fibrosing alopecia (FFA) [OR 6.92 (2.73–17.56), prevalence 5%], and central centrifugal cicatricial alopecia (CCCA) [OR 3.13 (1.03–9.49), prevalence 5%]. Hypothyroidism is more prevalent among patients with LPP [OR of 1.73 (1.24–2.42), prevalence 17%] and FFA [OR 1.86 (1.36–2.55), prevalence 19%]. LPP patients are prone to having dermatological diseases such as atopic dermatitis [OR 3.96 (1.14–13.81), prevalence 9%], lichen planus [OR 19.21 (1.47–251.02), prevalence 8%], psoriasis [OR 4.75 (2.04–11.06), prevalence 3%], and rosacea [OR 4.62 (2.96–7.19), prevalence 5%], while FFA patients are prone to having allergic contact dermatitis [OR 3.19 (1.44–7.08), prevalence 41%] and rosacea [OR 2.37 (1.72–3.29), prevalence 16%]. Coronary artery disease is found to be more common in LPP than controls [OR 1.63 (1.43–1.86), prevalence 8%], while dyslipidemia is more common among FFA [OR 1.41 (1.06–1.88), prevalence 20%] and CCCA [OR 4.46 (1.01–19.75), prevalence 54%] than controls, and diabetes mellitus is more prevalent among CCCA than controls [OR 1.67 (1.03–2.69), prevalence 26%]. While skin cancer [OR 2.22 (1.33–3.70), prevalence 2%] and melanoma [OR 4.46 (1.70–11.76), prevalence 1%] were found to be more common in LPP than controls, rheumatoid arthritis [OR 1.65 (1.09–2.51), prevalence 4%] was found to be more common in FFA than controls, and allergic rhinitis [OR 11.77 (1.55–89.24), prevalence 24%] and anxiety [OR 4.69 (1.29–16.98), prevalence 17%] were found to be more common in CCCA than controls.ConclusionsPatients with PCA are at higher risk of developing a wide range of comorbidities. Physicians should remain vigilant and conduct thorough investigations when clinical clues are present.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=564852, identifier CRD42024564852.